Business Analysis Enlargement of Mudcrab (Scylla Serrata) In Kepenghuluan Panipahan Laut, Sub-District Of Pasir Limau Kapas, District of Rokan Hilir, Riau Province - Syah, Hazlan; Yulinda, Eni; Hamid, Hamdi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research about business analysis enlargement of Mudcrab (Scylla Serrata) was conducted on February, 2016 in Kepenghuluan Panipahan Laut, Sub-District of Pasir Limau Kapas, District of Rokan Hilir, Riau Province. This study aims to (1) determine the input-output business enlargement of Mudcrab (Scylla Serrata), (2) analyzed the business enlargement of crab pond of Mudcrab (Scylla Serrata). The method used is a survey method that includes observation, interviews and documentation.Based on the results of research (1) stocking density in each pond with an area of 3x2-4x2 m as much as 200-300 crab / pond / crop with total production of 99,5-297,5 kg / pond / crop, (2) the average production costs incurred in enlargement business of Mudcrab (Scylla Serrata) with an area of 3x2-4x2 m of Rp 4.554.000, - / harvest up to Rp 15.714.000, - / harvest with total receipts received by Rp 9.950 million, - / harvest up to Rp 29.75 million, - / harvest and great benefits received Rp 5.396 million,-/ harvest up to Rp 14.036 million, - / harvest and (3) enlargement business of crab pond of Mudcrab (Scylla Serrata) in Kepenghuluan Panipahan Laut feasible with RCR value> 1, the FRR values> 6.02% and the value of PPC is between 1,46 to 1,54 per period or ± 8 months. Keywords : Enlargement Mudcrab, worthiness of business, Panipahan Laut